Age of No-Till System and Nitrogen Management on Common Bean Nutrition and Yield - Soratto, Rogério Peres [UNESP]; Perez, Adelson A. G. [UNESP]; Fernandes, Adalton M. [UNESP] (Amer Soc Agronomy, 2014)
In the no-till (NT) system, N availability may change depending on the number of years since NT was adopted. Thus, an experiment was conducted in a Typic Rhodudalf in Botucatu, Sao Paulo, Brazil, to evaluate the influence of the age (timing of establishment) of the NT system and N fertilizer management on the nutrition, yield, and N-use effciency (NUE) of common bean (Phaseolus vulgaris L.) crop. Treatments included four management systems (a newly implemented NT system, an established NT system, a newly implemented NT with an application of 60 kg ha(-1) N at pre-sowing, and an established NT with an application of 60 kg ha(-1) N at pre-sowing) and four N rates (0, 30, 60, and 120 kg ha(-1)) sidedressed at the V-4 stage of common bean. The age of the NT system did not affect common bean nutrition or its response to sidedressed N application, but the established NT system, regardless of N application at pre-sowing, provided a slightly greater common bean yield. In both the newly implemented and established NT systems, N fertilization increased the aboveground biomass, seed yield, and protein concentration in seeds. Even with the application of N at pre-sowing, seed yield increased in response to sidedressed N fertilization in all the management systems. The NUE by common bean was greater in treatments receiving N at pre-sowing. A higher seed yield and NUE of common bean grown in the NT systems after grass was achieved with the combined application of N at pre-sowing and sidedressing.